Typification and identity of species of Veronica subgenus Pseudolysimachium (Plantaginaceae) described from Belgium by A.L.S. Lejeune - Verloove, F. (Phytotaxa, 2017)
Three ‘ignored’ species of Veronica subgenus Pseudolysimachium (V. alternifolia, V. laxiflora and V. paludosa), described from Belgium by Alexandre Louis Simon Lejeune (1779-1858) at the beginning of the 19th century, are typified. Since no original material seems to be extant, neotypes are presented for these names. Their identity is briefly discussed and it is concluded that all are conspecific with V. longifolia s.l.